Improving thin-film polycrystalline CdSeTe/CdTe solar cell efficiencies through statistical design of experiments - Lustig, Zachary F., author; Sampath, Walajabad S., advisor; Sites, James R., committee member; Popat, Ketul C., committee member (Colorado State University. Libraries, 2022)
In recent decades, cadmium telluride (CdTe) solar photovoltaic (PV) technology has become increasingly popular to meet global energy demands. Its high throughput industrial fabrication methods, low material usage, recyclability, longevity, and theoretical maximum efficiency have led to its widespread integration in the PV sector. Most of the CdTe PV research reported in literature utilizes one-factor-at-a-time (OFAT) experiments. This work leverages statistical design of experiments (DOE) and statistical analysis of data to study the relationships between multiple processing factors and solar cell performance metrics. OFAT only indicates the primary effect of the chosen variable, whereas DOE determines the primary effect as well as the interaction effects. DOE determines both critical and insignificant factors, whereas OFAT assumes everything is a critical factor. DOE also requires fewer experiments, has more sophisticated predictive capabilities, and streamlines process optimization in comparison to OFAT. Since DOE is most effective with large data sets, the unique high throughput capability of the Advanced Research Deposition System (ARDS) at Colorado State University makes our lab a perfect candidate to utilize DOE for CdTe solar cell research. In this study, DOE and statistical analysis were used to investigate copper (Cu) doping, electrode painting, absorber deposition rate and temperature, p-doping of CdSe0.4Te0.6 (CST40) through arsenic (As) incorporation and tellurium (Te) overpressure, and oxide deposition at the back of the cell. Multiple linear regression (MLR) and analysis of variance (ANOVA) were conducted on all DOE's. An improved process was identified for the baseline high efficiency Cu-doped solar cells in which total process time was reduced by 33%. A thick 6µm structure of 18.5%+ efficiency was developed following statistical model suggestions. A standard procedure for electrode painting was developed. As a result of DOE, several 19%+ cells were fabricated achieving the highest efficiency of 19.44%. The best performing As doped CST40 graded CdTe cells of 18.5%+ were also fabricated using these methods. Carrier concentration versus voltage plots indicated successful p-doping of CST40 with As. Annealing the absorber with cadmium arsenide (Cd3As2) and depositing tellurium oxide (TeOx) at the back of the cell improved performance, yielding 80%+ fill factors. Decreasing thickness of CdTe behind CST40:As increased short-circuit current density to 30 mA/cm2+. Lastly, thinner absorbers yielded higher performance when backed with NiO:Cu.
Keywords: design of experiments; high efficiency; solar cells; doping; CdTe; optimization